PENINGKATAN MUTU KOMPOS KIAMBANG MELALUIAPLIKASI TEKNOLOGI HAYATI DAN KOTORAN TERNAK SAPI - Hartono, Joko S.S.; Same, Made; Parapasan, Yonathan (Jurnal Penelitian Pertanian Terapan, 2014)
Kiambang (Salvinia natans) which a water plant became a seriously problem in the use of Reservoir Batutegi, because nearly 80% of its surface covered by Salvinia natans. The presence of highly abundant of Salvinia natans have highly potential to be used as a source of organic fertilizer. The purpose of this study was to examine the effect of the application of biological technology (decomposers) and cow manure on the quality of the resulting compost kiambang. This study used randomized block design and experiment arranged in factorial 4 x 4 with three replications. The first factor was the dose of decomposers which consists of 4 levels, namely A1 = 0 ml, A2 = 20 ml, 30 ml dose = A3, and A4 = 40 ml decomposers per quintal kiambang respectively. The second factor was the dose of cattle dung, i.e. B1 = 0 kg, B2 = 10 kg, 20kg = B3, and B4 = 30 kg manure per quintal kiambang. The results showed the compost that has the best quality in terms of physical and chemical compost was the compost derived from the treatment of 30 ml and 40 ml decomposers per quintal kiambang which combined with 10 kg, 20 kg or 30 kg manure per quintal kiambang. Keywords: Salvinia natans, decomposers, cow manure, compost quality